Tingkat Persaingan Eksportir Utama Bunga Pala Bubuk di Pasar Internasional - Samhina, Lina; Lubis, Fadli Akbar; Rohmah, Fatkhiyah (JURNAL AGRIUST, 2025)
Indonesia is the largest producer and exporter of powdered nutmeg, competing with export countries, namely the Netherlands and Vietnam. This study aims to analyze the level of competitiveness and changes in the competitive position of Indonesian powdered nutmeg compared to two main competing countries, namely the Netherlands and Vietnam, in the international market. The data used is secondary data in the form of panel data for 2012–2024 with the Revealed Comparative Advantage (RCA) and Dynamic RCA (DRCA) analysis approaches. The analysis results show that Indonesia has a strong comparative advantage (RCA> 4) in the export of powdered nutmeg, but has experienced a downward trend in competitiveness of an average of -5% per year. In contrast, Vietnam and the Netherlands showed positive competitive growth, especially Vietnam, with a growth of 16% per year. The DRCA analysis shows that Indonesia's competitive position fluctuates, and in 2024, it is in a lost opportunity position, while Vietnam and the Netherlands are in a rising star position. These findings indicate that although Indonesia is a major exporter, its position is starting to be threatened by competitors. Policy suggestions to maintain and increase competitiveness require quality improvement strategies, post-harvest modernization, and strengthening export policies.